Strategi DP3KB Kabupaten Bintan Dalam Menangani kasus Kekerasan terhadap Anak - Noparia Sianipar; Wahjoe Pangestoeti; Okky Rizki Azizi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Violence against children is a problem that requires strategic and collaborative handling, considering that cases of child violence in Bintan Regency continue to show an increasing trend from 2024 to 2025. This study aims to analyze the strategy of the Women's Empowerment, Child Protection, Population Control and Family Planning (DP3KB) Office of Bintan Regency in handling violence against children and identify supporting and inhibiting factors for its implementation. The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with five purposively selected informants, documentation, and literature studies, which are analyzed using the interactive model of Miles and Huberman and John M. Bryson's strategic planning theory, with data validity tested through source triangulation and technical triangulation. The results of the study indicate that the strategies implemented consist of prevention strategies and handling strategies. Prevention strategies are carried out through socialization in schools and communities, empowerment of the Children's Forum, PATBM, and PUSPAGA, strengthening regional regulations, and digital-based violence prevention education. Handling strategies are carried out through complaint services, assessments, legal assistance, psychological services, rehabilitation, multidisciplinary referrals, and the Virtual Safe House innovation. Supporting factors for implementation include cross-sector synergy, local government commitment, organizational innovation capacity, and funding support, while inhibiting factors include limited human resources, limited regional budgets, the geographical conditions of the archipelago, and the rise in digital-based violence. This study concludes that the Bintan Regency DP3KB strategy has been quite effective and aligned with Bryson's strategic planning stages, but still requires strengthening institutional capacity, human resources, and budget support.